Labor Intensity of Tuberculosis Diagnosis and Sanitary and Hygienic Awareness of Patients with Drug-Resistant Forms of Pulmonary Tuberculosis - Jumaev Mukhtor Fatullaevich (Academia One Publishing, 2023)
Pulmonary tuberculosis is characterized by a wide variety of clinical symptoms, which vary widely in severity and severity. Usually, a direct relationship is noted between the severity of clinical symptoms and changes in the lungs, but their discrepancy is also possible: a severe tuberculous process and mild clinical symptoms or minor changes and a fairly vivid clinical picture. A sociological survey was conducted among 185 patients with drug-resistant forms of pulmonary tuberculosis aged 18–65 years who are being treated in the pulmonary tuberculosis departments of the hospital "Regional Clinical Anti-TB Dispensary" in the city of . Bukhara. According to the survey data, widespread, destructive forms of pulmonary tuberculosis with multidrug resistance of the pathogen prevailed among the examined patients. Most of the patients were rural residents of a young age, with a secondary education, unemployed, legally married, having bad habits, but at the same time well adapted in society and satisfactorily informed about tuberculosis
Keywords: drug resistance; mycobacteria; tuberculosis